2021
DOI: 10.1177/03000605211029058
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between air pollution levels in Madrid and the natural history of idiopathic pulmonary fibrosis: severity and mortality

Abstract: Objective We aimed to assess the relationship between major air pollutants and the natural history and mortality of idiopathic pulmonary fibrosis (IPF). Methods We conducted a retrospective cohort study from 2013 to 2019 among 52 patients with IPF from the pneumology department of a tertiary hospital. According to their geocoded residential address, each patient was assigned a mean concentration of carbon monoxide (CO), nitrogen dioxide, particulate matter 2.5 and 10, ozone, and sulfur dioxide, as measured at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Cigarette smoking, a common risk factor to some forms of ILD (IPF, 133 CPFE, 41 PLCH, 134 smoking‐related pulmonary fibrosis etc.) has been implicated in vascular remodeling and reduced NO production at the endothelial level, leading to endothelial dysfunction 135 ; but tobacco use might be just one of many intervening environmental agents alongside air pollution, 136 , 137 exposure to chemicals 138 and others. These environmental factors may be further compounded by social and economic factors: higher exposure of low‐income households to chemical substances and air pollution, reduced availability of healthy lifestyle choices such as exercise and salubrious diet, reduced access to medical care among others.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking, a common risk factor to some forms of ILD (IPF, 133 CPFE, 41 PLCH, 134 smoking‐related pulmonary fibrosis etc.) has been implicated in vascular remodeling and reduced NO production at the endothelial level, leading to endothelial dysfunction 135 ; but tobacco use might be just one of many intervening environmental agents alongside air pollution, 136 , 137 exposure to chemicals 138 and others. These environmental factors may be further compounded by social and economic factors: higher exposure of low‐income households to chemical substances and air pollution, reduced availability of healthy lifestyle choices such as exercise and salubrious diet, reduced access to medical care among others.…”
Section: Discussionmentioning
confidence: 99%
“…A large biobank study [36] found a dose-dependent association between progressive airflow obstruction and higher exposure to PM 2.5 , PM 10 and NO 2 , independently of other factors such as smoking and even in pre-COPD. In ILD, there is an association between exposure to NO 2 and decline in total lung capacity [37] and IPF incidence [38]; between O 3 [39,40] and NO 2 [40] concentrations and IPF exacerbations; and between PM 2.5 , PM 10 and CO exposure and IPF mortality [39,41]. Most of these associations are dose-dependent.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…Air pollution is increasingly recognized as an integral risk factor for fibrotic interstitial lung disease (fILD) or interstitial lung abnormality (ILA) incidence, baseline severity, progression, acute exacerbations, hospitalizations and mortality 1–23 …”
Section: Figurementioning
confidence: 99%
“…Of 24 studies investigating the impact of air pollution on fILD‐related outcomes, only 10 (42%) incorporated socio‐economic covariates in any analyses (Figure 1A). 1–24 Furthermore, the specific socio‐economic covariates included in these studies vary widely in their composition and ability to capture such a multifaceted social determinant of health (Figure 1B). It is imperative that future work establishes robust and reproducible methods for considering the synergistic impacts of environmental and socio‐economic factors in patients with fILD.…”
Section: Figurementioning
confidence: 99%